Studi Penempatan Sumur Resapan Berdasarkan Nilai Laju Infiltrasi, Kualitas Fisik Air dan Tekstur Tanah pada DAS Batang Arau Kota Padang - Dicky Maryand; Rusli HAR (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. The problem in this study is that there is a function change of land from forest areas, agricultural land and cultural heritage into residential land, the tendency for fast-saturated land, high rainfall intensity and frequent occurrence of inundation (flooding). Based on infiltration rate data, the average infiltration rate of the study area of 0.0914 cm/minute is included in the classification of very low recharge areas (<0.1 cm/minute). Therefore it is necessary to design infiltration wells by looking at the infiltration rate, physical quality of water and lithology of rocks. This research was conducted at 31 different points. The data obtained are primary data which are direct observations in the field, namely data on physical quality of water by using water checkers and secondary data, namely the infiltration rate and lithology of rocks.Based on statistical analysis, physical quality of water, rock lithology conditions and land use greatly affect the placement of infiltration wells. Planning placement of infiltration wells is located in residential, trading and service land areas with a number of 23 point infiltration wells that are spread downstream of the Batanng Arau Watershed, Padang City.Keywords:   Infiltration Rate, Physical Quality of Water, Lithology of Rocks, Land Use, Infiltration Wells